Faktor-faktor yang mempengaruhi keinginan orang tua menjadikan anak-anak mereka pegawai dibandingkan berwirausaha (Studi pedagang retail di pasar Bangkinang Kabupaten Kampar) - Arman, Arman (Jurnal Daya Saing, 2015)
Abstract: Lack of motivation of parents to make their children as an entrepreneur or self-employed is not no excuse. From the results wawacara conducted and analyzed can be found the reason why parents prefer their children to become civil servants compared to become entrepreneurs or self-employed as they (parents) that is running the business opened a shop which is on the market Bangkinang among others: because of the prestige or taste proud parents will be great with the civil servants and the official dress uniform when viewed into a pride, then the certainty of income attributed here that even small payments made to them, but they get certainty. When compared with no certainty though employers can sometimes be great, but sometimes not at all. Also due to old age or retired, retiree becomes a problem for people in this area because the retirement income when it is already limited and sometimes only hope of children who are still not clear as well that the PNS can be no guarantee of that. Then factor can be relied upon, as civil servants or work dikantoran, it will be more reliable in the deal, because the deal sometimes requires a strong and attractive appearance, so to be considered to facilitate civil servants dealing and or become reluctant. Keywords: keingian, Civil Servants, Entrepreneur